P-040 A comparison between particulate and Onyx embolization for devascularization of Juvenile angiofibromas prior to surgical resection. (4th July 2012) - Gemmete, J; Gao, M; Pandey, A; Chaudhary, N; Sullivan, S; McKean, E; Marentette, L
Abstract : Introduction: Juvenile nasopharyngeal angiofibroma is a locally invasive tumor in adolescent males. Surgical resection is the treatment of choice, but the tumor's extensive vascular involvement necessitates preoperative embolization. In this retrospective cohort, we compare the effectiveness of a novel liquid embolic agent, Onyx (ethylene vinyl alcohol copolymer), to traditional particulate embolic agents in reducing estimated blood loss (EBL) during surgical resection of Juvenile nasopharyngeal angiofibroma. Methods: We included 46 consecutive resections since 1995 for which preoperative embolization was either particulate (n=39) or Onyx only (n=7), and for which age at operation, date of operation, length of hospital stay, Fisch grade of tumor, resection approach, EBL during resection, and fluids during resection were available. In a subset of 26 resections, OR time was available. Results: The mean EBL for the Onyx group was 658.6±858.7 ml and the mean EBL for the particulate group was 1348.6±932.2 ml (one tailed Student t test p=0.043). The mean units packed red blood cells (PRBCs) used in the Onyx group 0.29±0.76 units (p=0.003) and the mean PRBCs used in the particulate cohort was 1.56±2.01. The relationship between embolization type, EBL and embolization type, PRBCs remained significant in the subset of patients with Fisch grade=III (Onyx n=4, particulate n=18, EBL p=0.001 and PRBCs p=0.045), and other Fisch categories did not have enough patients for a statistical analysis. The relationship between embolization type and EBL remained significant after correcting for age at operation (p=0.033). The proportion of resections for which an endoscopic approach was used was significantly higher in the Onyx group than the particulate group (71.4% and 20.5%; p=0.009), and this was also significant in the subset of patients with Fisch grade=III (p=0.040). Conclusion: Existing reports suggest that Onyx embolization decreases intraoperative EBL. Our study supports this result and also shows a reduction in units PRBC used intraoperatively. Although further studies are needed, Onyx appears to facilitate a less challenging surgical resection relative to traditional particulate embolization. Competing interests: None.